TRADITIONAL UZBEK EMBROIDERY HISTORY AND ANALYSIS OF THEIR SYMBOLIC MEANINGS - Nazarov Аbdulvohid Мamarasulovich; Nabiyeva Selme Iskandarоvna; Tоjibоyeva Muxtasarxоn Dilshоdjоn qizi (Journals Park Publishing, 2022)
This article provides a brief history of embroidery and an analysis of the history and symbolic meanings of Uzbek traditional patterns, as well as various methods and tools for sewing suzana embroidery, as well as an invaluable creative resource for designers. . This type of pattern and embroidery is still widely used in stylistic painting.
Keywords: artistic decoration; art of embroidery; ornament